Digital Optical Archiving of Medical Records in Hospital Information Systems - A Practical Approach towards the Electronic Patient Record? - Dujat, C.; Schmücker, P.; Haux, Reinhold; Winter, Alfred (Methods Inf Med, 1995)
The large number of inpatient and outpatient treatments in university hospitals leads to a high expense of medical documentation and consequently to an increasing number and size of medical documents. Due to legal regulations, these documents, which are mostly collected in patient-oriented folders (medical records), in general have to be stored for 30 years. This implies several spatial, organizational, and economical problems. Today, conventional archiving in hospitals often does not satisfy the medical needs to make available medical records for health care professionals in a systematic manner and in time. From 1989 to 1993 a prolective pilot study on ’digital optical archiving of medical records’ was carried out at Heidelberg University Hospital. The study results have made evident the feasibility of digital optical archiving in hospitals. Assumed that at least 40 percent of medical documents are originally produced in a digital format and that application systems generating these documents can be linked on-line to application systems for digital optical archiving via a communication system, it can be expected that the costs and organizational efforts for digital optical archiving will not exceed those of conventional archiving. In 1995, Heidelberg University Hospital will establish the information procedure ’digital optical archiving of medical records’. The digital optical archive will first be filled up with the medical records of the clinic for neurosurgery, and the endoscopic and sonographic films and reports of the clinic for internal medicine. The authors expect, that this procedure stepwise will lead to an integrated functionality on health (*) care professional workstations, to a hospital-wide use of medical documents, and to media-independent document management systems. The authors focus on the potentials of digital optical archiving, regarding this information procedure as an integral part of hospital information systems, and requirements on the systematic management of hospital information systems with respect to digital optical archiving. Keywords: Hospital information systems, medical records, archives, digital optical archiving, computer-based patient records.